Perioperative Management of Subdural Hemorrhage (SDH) Trepanation Decompression with Hemophilia A - Andika Satria Praniarda; Buyung Hartiyo Laksono (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2021)
Hemophilia is a serious inherited blood disease, transmitted by women, that affects mainly men and lasts for a lifetime. Hemophilia A is the most common form. If any of the factors necessary for blood clotting are absent or insufficient, the clotting mechanism is disturbed, causing insatiable bleeding. The most common cause of death in hemophilia patients is cerebral hemorrhage due to head trauma. In cases of intracranial hemorrhage, surgery should be performed immediately to obtain a better prognosis. A 17-year-old man diagnosed with a 2x4 loss of consciousness due to intracranial subdural hemorrhage (SDH) in the left frontotemporoparietal region and cerebral edema on day 4 accompanied by subfalcine herniation to the right with hemophilia A, planned trepanation decompression for SDH evacuation. The patient received 4000 units of factor VIII injection before surgery. Bleeding during surgery was 1100cc and he received a transfusion of 1940cc blood products until hemodynamically stable. In the postoperative phase, he was admitted to the ICU for 8 days, extubation was performed after the condition improved. In patient with hemophilia, evacuation of bleeding should be performed immediately, but there is a high risk of rebleeding. A recombinant factor VIII substitute should be administered immediately for the treatment of acute bleeding in patients with severe haemophilia A. Anesthetic maintenance should include reducing the risk of hypertension and tachycardia to minimize bleeding.